Upward Sloping Demand for a Normal Good? Residential Electricity in Arkansas - Fullerton, Thomas M.; Resendez, Ileana M.; Walke, Adam G. (International Journal of Energy Economics and Policy, 2015)
This study analyzes residential electricity demand in the state of Arkansas using an error-correction approach that examines both long-run and short-run dynamics. As in prior studies, results indicate that higher electricity prices reduce consumption in the long-run, but not in the short-run. With respect to variations in household income, residential electricity is treated as a normal good. The long-run income elasticity estimate is about twice as large as the short-run estimate. It is suggested that the muted short-run responses to price and income variables may reflect limited capacity to adjust the stock of electricity-consuming household devices over the short-term. More surprisingly, households are found to treat electricity as a normal good in the short-run, but have an upward sloping demand curve associated with it. The overall results suggest that increasing generating capacity in Arkansas will be feasible using the standard approach of incremental rate increases. Keywords: Residential Electricity Consumption; Regional Economics; Business Economics JEL Classifications: M21; Q4; R15